ANALISIS SPASIAL KETERJANGKAUAN FASILITAS KESEHATAN OLEH PENDUDUK DI KECAMATAN SUKASARI MENGGUNAKAN GIS - Aurellia Bintang Maulana; Artia Regita fitrianto; Dzikrina Nurul Fathia; Abdullah Azzam Izzuddin (Universitas Nusa Cendana, 2026)
This study aims to analyze the accessibility of health facilities by the population in Sukasari District using a Geographic Information System (GIS) approach. Sukasari District was selected due to its urban characteristics with relatively high population density and mobility, making the need for health services critical. The study employed a quantitative method with a GIS-based spatial approach, supported by questionnaire distribution to 47 respondents. Analysis was conducted on aspects of distance, travel time, road conditions, transportation availability, and the distribution of health facilities. Results indicate that the majority of respondents considered health facilities in their area to be well-distributed and sufficiently accessible. Most respondents stated that the nearest health facility is less than 2 km away with a travel time of less than 15 minutes. Road conditions and transportation availability were also rated as adequately supportive of community access to health services. Nevertheless, some areas were found to have unequal access quality, particularly regarding infrastructure and transportation conditions. Cost factors also remained a consideration for some community members in utilizing health services. Overall, this study demonstrates that the level of accessibility to health facilities in Sukasari District is relatively good, though equalization of access quality, infrastructure improvement, and affordability of health services still need attention to ensure equitable access for all residents.